2016
DOI: 10.18632/oncotarget.12892
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of the toll-like receptor 3 promotes metabolic reprogramming in head and neck carcinoma cells

Abstract: In this study, a possible link between the innate immune recognition receptor TLR3 and metabolic reprogramming in Head and Neck carcinoma (HNC) cells was investigated. The effects of TLR3 stimulation/knock-down were assessed under several culture conditions in 4 HNC cell-lines by cell growth assays, targeted metabolomics, and glycolysis assays based on time-resolved analysis of proton release (Seahorse analyzer). The stimulation of TLR3 by its synthetic agonist Poly(A:U) resulted in a faster growth of HNC cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 44 publications
(50 reference statements)
0
23
0
Order By: Relevance
“…The expressions of some TLRs and HIF-1α correlate [104,119] and prominent expression of HIF-1α, TLRs, and CAIX can be found as early as in PanINs [104]. Conversely, TLR3 was shown to induce the Warburg effect and aid tumor cells in adapting to the hypoxic milieu [102], whereas HIF-1α and TLR4 may synergistically promote development of pancreatic cancer [119].…”
Section: Inflammation As An Inherent Feature Of Pancreatic Cancer Andmentioning
confidence: 98%
See 1 more Smart Citation
“…The expressions of some TLRs and HIF-1α correlate [104,119] and prominent expression of HIF-1α, TLRs, and CAIX can be found as early as in PanINs [104]. Conversely, TLR3 was shown to induce the Warburg effect and aid tumor cells in adapting to the hypoxic milieu [102], whereas HIF-1α and TLR4 may synergistically promote development of pancreatic cancer [119].…”
Section: Inflammation As An Inherent Feature Of Pancreatic Cancer Andmentioning
confidence: 98%
“…Damage-associated molecular patterns (DAMPs) are released upon stress, e.g., cellular injury, inflammation, or tissue damage [101] to stimulate toll-like receptors (TLRs), a subgroup of pattern recognition receptors (PRRs). TLRs enable cancer cells to undergo the switch from oxidative phosphorylation to glycolysis [102] and drive pancreatic stromal inflammation [103]. Toll-like receptor expression depends on PanIN grade [104], increases as cancer progresses [105], and is associated with metastases [106].…”
Section: Inflammation As An Inherent Feature Of Pancreatic Cancer Andmentioning
confidence: 99%
“…reported that the TLR signaling pathway promoted cell proliferation of pancreatic cancer, emphasizing a particular role of TLR2, TLR‐4, and TLR‐9 in the process . Likewise, TLR3 was found to stimulate cancer cell survival, proliferation, and progression in cancers of the pharynx, breasts and head and neck . For lung cancer, the TLR pathway may play a key role in tumorigenesis and progression, especially for NSCLC .…”
Section: Introductionmentioning
confidence: 98%
“…14 Likewise, TLR3 was found to stimulate cancer cell survival, proliferation, and progression in cancers of the pharynx, 15 breasts 16 and head and neck. 17 For lung cancer, the TLR pathway may play a key role in tumorigenesis and progression, especially for NSCLC. [18][19][20] Therefore, some genetic variants in genes of this pathway may have a predictive value as a clinically potential biomarker for outcomes of NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…59 As a family, TLRs are expressed by multiple immune cells, including macrophages, dendritic cells (DCs), B cells, and natural killer (NK) cells, as well as by non-immune cells including epithelial cells, fibroblasts and malignant cells. [60][61][62] Thus, besides controlling the activation, maturation and immunological functions of immune cells (notably cytokine secretion), [63][64][65][66][67][68][69] TLR signaling can influence tumor metabolism, proliferation and dissemination.- 60,62,[70][71][72][73][74][75] Several TLR ligands demonstrated potential therapeutic efficacy against malignant disorders. 70,76 Imiquimod, also called Aldara® (imiquimod 5% cream as commercialized by 3M Pharmaceuticals) or R-837, is a TLR7 agonist that is approved by the US Food and Drug Administration (FDA) for the treatment of actinic keratosis, external genital/perianal warts (condylomata acuminata), and superficial basal cell carcinoma.…”
Section: Introductionmentioning
confidence: 99%